Lexical Transformations in Song Translation: A Qualitative Study of Lana Del Rey’s Lyrics - Salma Mufidah; Sajarwa Sajarwa (GLENS: Global English Insights Journal, 2026)
This study examines lexical transformations in the Indonesian translation of Lana Del Rey’s song lyrics, focusing on how meaning is reconfigured to maintain naturalness and stylistic quality in the target language. A qualitative descriptive method was employed through the analysis of five selected songs from the LyricsTranslate website. The songs were selected for their extensive use of cultural references, figurative language, and metaphorical expressions. A total of 110 instances of lexical transformation were identified and analysed based on categories of lexical substitution, compensation, metaphorical transformation, and zero transformation. The findings show that lexical substitution, particularly modulation, is the most frequently employed strategy, followed by specification, generalization, and differentiation. Compensation and metaphorical transformation are also used to address cultural and stylistic differences between the source and target languages. The study indicates that the translations prioritise communicative clarity and natural expression over literal equivalence. Overall, lyric translation involves not only linguistic transfer but also semantic and stylistic adaptation. However, the findings should be interpreted cautiously due to the use of unofficial online translations and the limited number of songs analysed.